Synthesis of CdSE quantum-dots-sensitized TiO2 nanocomposites with visible-light photocatalytic activity - Yong, S.; Ke, J.; Zhao, Q.; Li, Xin Yong; Zheng, N.; Xue, F. (Trans Tech Publications, 2014)
CdSe Quantum Dots (QDs) sensitized TiO2 photocatylysts were synthesized by a facile sol-gel method at room temperature. The effects of CdSe QDs concentration on the properties of the photocatalysts were studied by XRD, BET, SEM, UV/vis. The photocatalytic performance was investigated by degrading methylene blue (MB) under halogen-tungsten lamp irradiation. The results revealed that the catalysts doped with CdSe QDs show large surface area, small crystal size and narrow band gap. The catalysts doped with 0.05% CdSe QDs possessed the best activity, and the degradation efficiency of methylene blue (MB) is up to 99.2% within 180 min.